Effect of salt contents on enzymatic activities and halophilic microbial community structure during phenanthrene degradation. (May 2016) - Guo, Guang; He, Fen; Tian, Fang; Huang, Yong; Wang, Hui
Abstract: The halophilic bacteria could be useful for bioremediation of polycyclic aromatic hydrocarbons (PAHs) pollution in hypersaline environments, which has posed a significant environmental problem. The effect of salt contents on a halophilic bacterial consortium, which was enriched from an oil-contaminated saline soil, was investigated. At 20 per cent salt contents, the consortium maintained lower PAHs dioxygenase (PDO), catechol 2, 3-dioxygenase (C23O) and catechol 1, 2-dioxygenase (C12O) activity than at 10 per cent salt contents before complete degradation. Pyrosequencing results indicated that the predominant bacteria were closely related to genera Thalassospira, Rhodobium, Mariprofundus and Psychroflexus at 10 per cent salt contents, while at 20 per cent salt contents, the dominant bacteria were Chromohalobacter and Methylohalomonas, suggesting some bacteria could not survive at higher salt contents. Increased salt contents decreased the diversity of the bacterial consortium and favored the growth of bacteria in class Gammaproteobacteria . Three-dimensional excitation-emission matrix fluorescence spectra (3DEEMs) showed that elevated salt contents also made some intermediate products accumulated during degradation and then lowered the phenanthrene degradation rate. This study extended the knowledge on decontamination of PAHs in saline environments by an applicable halophilic bacterial consortium. Highlights: A bacterial consortium degrading phenanthrene was enriched at high salt contents. Elevated salt contents decreased degradation rate. The effect of salt on the three enzymes was first studied. Elevate salt contents changed the community structures and the degradation pathway. The consortium was dominated by known and unknown PAHs-degrading bacteria.